An An Algorithm for Fuzzy Soft Set Based Decision Making Approach - Mohammed, Shehu Shagari; Azam, Akbar (Yugoslav Journal of Operations Research; Vol 30 No 1 (2020), 2019)
The notion of soft set theory was initiated as a general mathematical tool for handling ambiguities. Decision making is viewed as a cognitive-based human activity for selecting the best alternative. In the present time, decision-making techniques based on fuzzy soft sets have gained enormous attention. On this development, we propose a new algorithm for decision making in the fuzzy soft set environment by hybridizing some existing techniques. The other novelty is the idea of absolute scores. The second concerns the concept of priority table in group decision-making problems. The advantages of our approach herein are stronger power of objects discrimination and a well-determined inference